Development Of Teaching Material To Support Merdeka Curriculum On Stoichiometry For Phase F - Damiyanti, Damiyanti; Mawardi, Mawardi; Suryani, Okta (Universitas Pendidikan Mandalika, 2024)
This study aims to develop teaching materials to support merdeka curriculum learning on stoichiometry material phase F SMA / MA. This research uses the Eduactional Design Research (EDR) method with the Plomp development model which consists of three stages, namely the preliminary research stage, the development or prototyping phase, and the trial and assessment phase. Data collection was carried out using validity and practicality questionnaires. The subjects of this study were three chemistry lecturers, two chemistry teachers and nine students with high, medium and low ability levels. The validity questionnaire was given to three chemistry lecturers and two chemistry teachers while the practicality questionnaire was given to two chemistry teachers and nine students. The results showed that the validity test obtained a validity value of 88% which was declared a valid category. While the results of the practicality test for chemistry teachers obtained a value of 91% which was declared a very practical category and the results for students obtained a value of 93% which was declared a very practical category. Based on the results of the study, it was found that the development of teaching materials to support merdeka curriculum learning in SMA/MA phase F stoichiometry material was valid and practical